Cross-correlation-regressive analysis of resource descriptions of difficult wares - Маловик, Константин Николаевич; Скатков, Иван Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The method of cross-correlation-regressive analysis of resource descriptions of difficult wares is developed. Offered approach illustrated by an example.